2014
DOI: 10.1186/1471-2334-14-439
|View full text |Cite
|
Sign up to set email alerts
|

Off-treatment virologic relapse and outcomes of re-treatment in chronic hepatitis B patients who achieved complete viral suppression with oral nucleos(t)ide analogs

Abstract: BackgroundThe durability of off-treatment virologic responses has not been fully elucidated in chronic hepatitis B (CHB) patients who have previously achieved complete virologic suppression with nucleos(t)ide analog (NA) therapy. This study aimed to assess off-treatment virologic relapse rates and to characterize the outcomes of subsequent re-treatment in CHB patients who have discontinued oral NA following complete virologic suppression.MethodsNinety-five CHB patients who showed complete virologic suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 31 publications
2
81
1
5
Order By: Relevance
“…Some studies have found longer time to and lower rate of HBV DNA negativity in the subgroups of patients with e antigen positivity and higher baseline HBV DNA level [11,13,15,17], but others have not as in our study [18,19]. Studies have also found that previous NA exposure, age more than 60 years and the presence of cirrhosis do not influence viral suppression during prolonged therapy as our study [4,13,18,20].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Some studies have found longer time to and lower rate of HBV DNA negativity in the subgroups of patients with e antigen positivity and higher baseline HBV DNA level [11,13,15,17], but others have not as in our study [18,19]. Studies have also found that previous NA exposure, age more than 60 years and the presence of cirrhosis do not influence viral suppression during prolonged therapy as our study [4,13,18,20].…”
Section: Discussioncontrasting
confidence: 61%
“…This indicates its ineffectiveness in clearing the cccDNA which is regarded as the hallmark of complete viral [5,7,16,19]. In such studies, a HBV DNA cutoff level of 20 to 2000 IU/mL was considered for stopping or restarting therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…In total, 2332 (each study contribution from 11 to 401) patients were included in the 25 studies. All but one were cohort studies (three prospective, one retrospective‐prospective, and 20 retrospective, while one was a randomized study comparing the effects of 12 versus 24 months of additional therapy after response to lamivudine in HBeAg‐negative CHB . One study was found to have high quality, 14 to have acceptable quality, and 10 to have low quality based on their risk of bias assessments (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation